A Multi-National Human–Computer Interaction Evaluation of the Public Participatory GIS GeoCitizen - Bartling, Mona; Resch, Bernd; Eitzinger, Anton; Zurita-Arthos, Leo (Osterreichische Akademie der Wissenschaften, Verlag, 2019)
Designing user-friendly Public Participatory Geographic Information Systems (PPGIS) is a challenging task, since a PPGIS is typically used by users who have different characteristics and different requirements and needs. Hence, applying Human–Computer Interaction (HCI) principles is of particular importance in designing PPGIS. This study aims to create an inventory of usability aspects of a PPGIS by focusing on understanding the characteristics of a broad range of users. The usability study included 73 participants from Colombia, Uganda and Austria. We combined a custom qualitative survey (conducted in all three countries) with an eye-tracking based survey (conducted only in Austria). Considerable usability problems were faced especially by participants with low levels of IT-literacy. This was mostly due to a lack of experience in using functionally complex smartphone applications or interactive maps. In general, we observed a high level of difference in usability between the user groups. The eye-tracking statistics for the Austrian study supported the outcomes of the qualitative survey well.